American Exceptionalism, and Jasmine’s Agency and Self-identity in Bharati Mukherjee’s Jasmine - Baral, Pawan (Pursuits: A Journal of English Studies, 2023)
The paper examines the development of Jasmine’s agency and self-identity in her all avatars – Jyoti, Jasmine, Jazzy, Jane and Jase – during her odyssey from Hasnapur to Iowa. Drawing and departing different critics and thinkers like James W. Ceaser, Johannes Thimm, and Stephen M. Walt, it shows whether American ideology fortifies her becomingness of a self-willed female protagonist in her troublesome life experience of poverty, exile and immigration. Hence, the paper argues that her the agency and self-identity to act on her own freewill remains all the same even to the end despite being exposed to the American ideals of liberty, egalitarianism, individualism, republicanism, democracy and laissez faire economics. American exposure does not significantly change her determination and spirit that she has shown while boldly denying the prediction of her widowhood and exile by shouting at the astrologer. Hence, the paper argues that her the agency and self-identity to act on her own freewill remains all the same even to the end.